2023
DOI: 10.1002/aenm.202301158
|View full text |Cite
|
Sign up to set email alerts
|

NNaTaO3@Ta3N5 Core‐Shell Heterojunction with Controlled Interface Boosts Photocatalytic Overall Water Splitting

Abstract: Ta3N5 is a promising material for photocatalytic hydrogen production from water because of its suitable band structure for both solar energy collection and overall water splitting, while its application is restricted by severe charge recombination as well as non‐equilibrium redox capabilities. Herein, atomic‐scale N‐doped NaTaO3@Ta3N5 (NNaTaO3@Ta3N5) core‐shell cubes prepared by nitridation of cubic NaTaO3 are reported. The core‐shell heterojunction cubes present efficient and stoichiometric evolution of H2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…In the case of the Ca 2p spectra in Figure d, the Ca 2p 3/2 and Ca 2p 1/2 doublet peaks appear at 345.5 and 349.3 eV, respectively, and the areas of these peaks are almost unchanged following the renitriding process. Figure c displays Ta 4f high-resolution XPS data, which contain two groups of doublet peaks at 26.7/24.8 and 25.7/23.8 eV, corresponding to Ta–N and Ta–O bonds, respectively . It should be noted that the intensity of the Ta–N peaks increases with increasing heating time during the renitridation, indicating a greater degree of nitridation of the NCTON, in accordance with the N 1s XPS and XRD results.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In the case of the Ca 2p spectra in Figure d, the Ca 2p 3/2 and Ca 2p 1/2 doublet peaks appear at 345.5 and 349.3 eV, respectively, and the areas of these peaks are almost unchanged following the renitriding process. Figure c displays Ta 4f high-resolution XPS data, which contain two groups of doublet peaks at 26.7/24.8 and 25.7/23.8 eV, corresponding to Ta–N and Ta–O bonds, respectively . It should be noted that the intensity of the Ta–N peaks increases with increasing heating time during the renitridation, indicating a greater degree of nitridation of the NCTON, in accordance with the N 1s XPS and XRD results.…”
Section: Resultssupporting
confidence: 77%
“…In other work, Lu et al. reported that modification to increase the nitrogen content is a promising means of tuning charge transfer characteristics to enhance photocatalytic overall water splitting …”
Section: Introductionmentioning
confidence: 99%
“…46,51 With the assistance of Rh@CrO x core–shell cocatalyst, the solar-to-hydrogen efficiency for overall water splitting of the reported Ta 3 N 5 -based semiconductor photocatalyst has achieved 0.09%. 52 In addition to the orthorhombic Ta 3 N 5 , the hexagonal TaN has also shown potential applications in various photocatalytic reactions. 53…”
Section: Photocatalytic Functions Of Transition Metal Nitridesmentioning
confidence: 99%
“…52,78 For instance, it has been reported that this N-doped NaTaO 3 /Ta 3 N 5 core–shell heterojunction facilitates the smooth and rapid migration of photogenerated charge carriers to the surface active sites. 52 Additionally, the combination of different materials in the heterojunctions can leverage the advantages of each component, thereby achieving enhanced photocatalytic performance. Depending on the specific photocatalytic reaction, the surface of TMN photocatalysts can be loaded with reducing co-catalysts or oxidizing co-catalysts.…”
Section: Design Strategies Of Transition Metal Nitride Catalystsmentioning
confidence: 99%
See 1 more Smart Citation